Analysis of TikTok social media's impact on bullying behavior among students of SDN 13 Pekanbaru - Tenesya Dara Saski; Muhamad Nukman (Inovasi Kurikulum, 2025)
The emergence of digital technology, especially social media, has changed many aspects of human life, including education. Elementary school students widely use social media and have been significantly influenced by it. This study aims to identify and analyze the relationship between bullying behavior and social media use among elementary school children, with a focus on students' self-confidence. This study used a descriptive quantitative research method. The study was conducted at SD Negeri 13 Pekanbaru, with the research subjects comprising high-level students in grades IV, V, and VI. The data collection techniques include population and sample determination, development of research instruments (questionnaires), distribution of questionnaires to the research sample, data collection, and data analysis. The findings of the study indicate that the influence of social media on bullying behavior can lower the self-esteem of students who experience bullying, as well as hinder the growth of social skills and all aspects of students' personal lives, including low self-esteem, stress and anxiety, depression, social isolation, difficulty focusing, and poor academic performance.   Abstrak Kemunculan teknologi digital, terutama media sosial telah mengubah banyak aspek kehidupan manusia, termasuk pendidikan. Media sosial telah banyak digunakan oleh murid sekolah dasar dan memberikan pengaruh cukup besar dalam karakter murid. Penelitian ini bertujuan untuk mengidentifikasi dan menganalisis hubungan antara perilaku bullying dan penggunaan media sosial di kalangan anak SD yang berfokus pada nilai kepercayaan diri murid. Dalam penelitian ini digunakan metode penelitian kuantitatif deskriptif. Pelaksanaan penelitian ini berlangsung di SD Negeri 13 Pekanbaru dengan subjek penelitian terdiri dari murid tingkat tinggi yaitu kelas IV, V, dan VI. Teknik pengumpulan data adalah penentuan populasi dan sampel, pengembangan instrumen penelitian berupa kuesioner, pendistribusian kuesioner kepada sampel penelitian, pengumpulan data, dan analisis data. Temuan penelitian menunjukkan bahwa pengaruh media sosial terhadap perilaku bullying dapat menurunkan harga diri murid yang mengalami bullying, serta menghambat pertumbuhan keterampilan sosial dan semua aspek kehidupan pribadi murid, termasuk harga diri yang rendah, stres dan kecemasan, depresi, isolasi sosial, kesulitan fokus, dan kinerja akademik yang buruk. Kata Kunci: guru sekolah dasar; media sosial; perilaku perundungan